Effectiveness of Gentamicin and Chloramfenicol for Infant Dacryocistitis - Indrajati, Christina; Handojo, Norma D.; Winarto, Winarto (Fakultas Kedokteran; Universitas Islam Sultan Agung (UNISSULA), 2011)
Background: Dacryocistitis is an infection of lacrimal system due to blockage of Hasner valve by a membrane commonly found in infant. The management of dacryocistitis includes nasolacrimal massage and topical broad spectrum antibiotics since chloramfenicol and gentamicin are widely used in regional hospital primary health care in Indonesia, the effectiveness of the two antibiotics require an assessment. This study was conducted to compare the clinical and bacteriological effectiveness of gentamicin and chloramfenicol for infant dacryicistitis to describe the etiologic bacterial and its sensitivity pattern.Design and Method: A randomized control trial study included 46 patients divided equally into two groups. Group K received one drop chloramfenicol six times per day and group G receive one drop gentamicin six times per day. Both of groups received therapy for 14 days. Clinical evaluation was done on week I and week II. Microbiological evaluation was performed before treatment and at the end of week two. Criteria for clinical recovery were the disappearance of the sign and symptoms of dacryocistitis, while microbiologic recovery ruled out when there is no bacteria find out on secret and lacrimal system. Antibiotics eye drop was applied after digital massage on lacrimal system and clean the secret. Grams staining, bacterial culture and sensitivity test were performed in microbiology laboratory.Result: Clinical and microbiological recovery for chloramfenicol and gentamicin were 43.5% (p = 0.832) and 52.2% (p = 0.670) respectively. The most frequent bacteria on infant dacryocistitis were Staphylococcus aureus (45.7%) followed by Pseudomonas (21.7%), Enterobacter sp (17.4%), Escherichia coli (10.9%) and Staphylococcus epidermidis (4.3%). The sensitivity of bacteria against chloramfenicol and gentamicin was Staphylococcus aureus 57.1%, Pseudomonas aeruginosa 50%, Enterobacter sp 87.5%, Escherichia coli 40% and Staphylococcus epidermidis 100%.Conclusion: There is no significant different between chloramfenicol and gentamicin in dacryocistitis (Sains Medika, 3(2):105-111).